2019
DOI: 10.1186/s12935-019-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

ITK inhibition induced in vitro and in vivo anti-tumor activity through downregulating TCR signaling pathway in malignant T cell lymphoma

Abstract: Background Angioimmunoblastic T cell lymphoma (AITL) is a distinct subtype of peripheral T cell lymphoma and associated with poor outcomes. The activation status of T cell receptor (TCR) signaling has recently become a focus of attention in terms of the therapeutic targets. However, the molecular pathogenesis mechanisms and novel therapeutic targets are largely unknown. Methods Antibodies specific to phosphorylated ZAP70, ITK and PLCγ1 were used to identify the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…A disruption of the interactions between antigen-presenting cells and T cell lymphomas may decrease lymphoma growth rates and may attenuate lymphoma-induced NK cell inhibitions. Also, drugs that interfere with cascades downstream of the TCR such as ITK inhibitors may produce similar outcomes [ 16 ]. Lastly, boosting NK cell numbers and/or functions in vivo [ 17 ] or transferring ex vivo-expanded NK cells as applied to patients with AML [ 18 ] may also be of use in the treatment of T cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…A disruption of the interactions between antigen-presenting cells and T cell lymphomas may decrease lymphoma growth rates and may attenuate lymphoma-induced NK cell inhibitions. Also, drugs that interfere with cascades downstream of the TCR such as ITK inhibitors may produce similar outcomes [ 16 ]. Lastly, boosting NK cell numbers and/or functions in vivo [ 17 ] or transferring ex vivo-expanded NK cells as applied to patients with AML [ 18 ] may also be of use in the treatment of T cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that a compound heterozygous missense mutation and a large deletion in the KCTD7 gene presenting as an opsoclonus-myoclonus ataxia-like syndrome [ 35 ]. In addition, Liu et al demonstrated that the inhibition of ITK can induce anti-tumor activity by downregulating TCR signaling pathway in malignant T cell lymphoma both in vitro and in vivo [ 36 ]. All these researches indicated that these 9 optimal genes might be involved in the occurrence and development of human diseases including OP.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular T-cell receptor signaling via increased phospho-ITK expression is known to be associated with inferior prognosis in T-cell lymphomas, and ITK inhibition has been shown to prime apoptosis of malignant T cells by downregulating anti-apoptotic proteins, including Bcl-2, MCL-1, and Bcl-XL. 12 At the protein level, in patient A expression of Mcl-1 and Bcl-2 was induced during venetoclax monotherapy, but was reduced upon combinatorial treatment. In contrast, patient B showed a predominant induction of pro-apoptotic BH3 family members in response to combined ibrutinib and venetoclax treatment ( Online Supplementary Figure S3C and D ).…”
mentioning
confidence: 94%